2022
DOI: 10.3390/metabo12030222
|View full text |Cite
|
Sign up to set email alerts
|

Can Exercise Training Alter Human Skeletal Muscle DNA Methylation?

Abstract: Skeletal muscle is highly plastic and dynamically regulated by the body’s physical demands. This study aimed to determine the plasticity of skeletal muscle DNA methylation in response to 8 weeks of supervised exercise training in volunteers with a range of insulin sensitivities. We studied 13 sedentary participants and performed euglycemic hyperinsulinemic clamps with basal vastus lateralis muscle biopsies and peak aerobic activity (VO2 peak) tests before and after training. We extracted DNA from the muscle bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Note: we only had OMIC data available at the transcriptomic level following muscle disuse. Note 2: summary statistics for the exercise‐ and disuse‐induced mRNA changes came from two recent meta‐analyses (Fanelli et al, 2017 ; Garcia et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Note: we only had OMIC data available at the transcriptomic level following muscle disuse. Note 2: summary statistics for the exercise‐ and disuse‐induced mRNA changes came from two recent meta‐analyses (Fanelli et al, 2017 ; Garcia et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various groups, including our own, have looked at the role of DNMTs in insulin resistance. In our study, we showed that the mRNA expression of DNMTs was unaffected by 8-weeks of exercise training in the skeletal muscle of volunteers with a range of insulin sensitivities ( 63 ). Moreover, a study in pancreatic islets from human donors with and without T2DM revealed no gene expression difference for DNMT1 and DNMT3B ( 64 ).…”
Section: Introductionmentioning
confidence: 77%
“…Note : we only had OMIC data available at the transcriptomic level following muscle disuse. Note 2 : summary statistics for the exercise- and disuse-induced mRNA changes came from two recent meta-analyses 24,25 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we performed a series of OMIC integrations and pathway analyses to identify the molecular pathways affected by age, VO2max, exercise training, and/or muscle disuse across both OMIC layers.Note: we only had OMIC data available at the transcriptomic level following muscle disuse. Note 2: summary statistics for the exercise-and disuse-induced mRNA changes came from two recent meta-analyses24,25 .…”
mentioning
confidence: 99%